Pengaruh Promosi Berbasis Media Sosial dan Kualitas Produk terhadap Keputusan Pembelian : Survei pada Konsumen Aliya Cake’s Karangnunggal - Yuliani, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the Effect of Social Media-Based Promotion and Product Quality on Purchase Decisions (Survey on Aliya Cake`s Karangnunggal Consumers). The research method uses a quantitative method with a survey approach, a survey in this study to consumers of Aliya Cake`s Karangnunggal with a sample of 100 people. The data used are primary and secondary data. The data analysis technique used is Multiple Linear Regression Analysis using SPSS version 25 software. The results show that simultaneously Social Media-Based Promotion and Product Quality have a significant influence on Purchase Decisions. Partially, Social Media-Based Promotion has a significant influence on Purchase Decisions. Partially, product quality has a significant effect on purchasing decisions.